2020
DOI: 10.1002/ps.6165
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of glycerate kinase (GLYK) into Metarhizium acridum increases virulence to locust

Abstract: BACKGROUND Improvements in the virulence of the fungal pathogen Metarhizium acridum can crucially promote its efficacy to control locusts and grasshoppers. The polysaccharide components of the cell wall remarkably contribute to fungal virulence. RESULTS Here we found that M. acridum lacked the gene families of glycerate‐3‐kinase (GLYK) as the synthesis enzymes of saccharides. We then generated mutants by introducing the GLYK gene from the host‐generalist M. robertsii into the host‐specialist M. acridum. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…[91][92][93][94][95] A previous study showed that an increase in cell wall mannans enhanced the virulence of M. acridum, with a higher expression of PGRP-LE and GNBP3 but lower expression of defensin (downstream of PGRP and GNBP3) and PO activity in locust. 96 The cell wall surface mannose and chitin containing carbohydrate motifs in hyphal bodies of CQMa421 were more densely distributed relative to CQMa102, which may contribute to the induction of different immune responses during locust infection by the two Metarhizium species. In addition, the mobilization of immune responses for infection control requires considerable energy and resource allocation by the host.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…[91][92][93][94][95] A previous study showed that an increase in cell wall mannans enhanced the virulence of M. acridum, with a higher expression of PGRP-LE and GNBP3 but lower expression of defensin (downstream of PGRP and GNBP3) and PO activity in locust. 96 The cell wall surface mannose and chitin containing carbohydrate motifs in hyphal bodies of CQMa421 were more densely distributed relative to CQMa102, which may contribute to the induction of different immune responses during locust infection by the two Metarhizium species. In addition, the mobilization of immune responses for infection control requires considerable energy and resource allocation by the host.…”
Section: Discussionmentioning
confidence: 92%
“…Most fungal mannans and chitins are recognized by the host system through membrane‐bound receptors, leading to the stimulation of different host immune pathways 91–95 . A previous study showed that an increase in cell wall mannans enhanced the virulence of M. acridum , with a higher expression of PGRP‐LE and GNBP3 but lower expression of defensin (downstream of PGRP and GNBP3 ) and PO activity in locust 96 . The cell wall surface mannose and chitin containing carbohydrate motifs in hyphal bodies of CQMa421 were more densely distributed relative to CQMa102, which may contribute to the induction of different immune responses during locust infection by the two Metarhizium species.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolites released from hyphal bodies are targeted to muscle or immune tissues, such as fat bodies ( Figure 3 ). The tryptamine synthesized by the specialist species M. acridum targets the aryl hydrocarbon receptor AhR of fat bodies in locusts to produce reactive oxygen species (ROS) and suppress immune response genes, including cactus , stubble , and easter [ 103 ]. Mycotoxin destruxin A, which is produced by generalist species such as M. anisopliae but not specialist species such as M. acridum , induces visceral muscle contraction in locusts through its effect on the influx of extracellular Ca 2+ [ 104 ].…”
Section: The Late-phase Interactionmentioning
confidence: 99%
“…Biocontrol applications include a number of developments in bacteria, e.g., Burkholderia pyrrocinia (He et al, 2018) and fungi, e.g., Beauveria bassiana, Metarhizium acridum, Trichoderma harzianum, Isaria fumosorosea (Kim et al, 2013;Hu and Wu, 2016;Xia et al, 2018;Tong et al, 2021;Asgari, 2023), which are modified to enhance the efficacy of known biocontrol agents to control different pests or pathogens. Some of these applications express RNAs which trigger a RNAi-based response in the exposed target pests to achieve a biocontrol effect.…”
Section: Gm Microorganismsmentioning
confidence: 99%
“…Some of these applications express RNAs which trigger a RNAi-based response in the exposed target pests to achieve a biocontrol effect. Others express different types of effector molecules like chitinases (Xia et al, 2018), glycerate-3-kinase (Tong et al, 2021) or bumblebee venom serin proteases (Kim et al, 2013). However, also bacteria and fungi that are not commonly used for biocontrol may be developed into GM biocontrol agents, e.g., Escherichia coli strains with modifications to express RNA-molecules which trigger RNAi mechanisms (Xiong et al, 2013;Vatanparast and Kim, 2017;Niño-Sánchez et al, 2021).…”
Section: Gm Microorganismsmentioning
confidence: 99%